Incumbent Banks Vs New Entrants: The Impact of Peer-To-Peer Lending and Market Power on The Stability of Islamic Commercial Banks - Sholihin, Anwarul (Likuid Jurnal Ekonomi Industri Halal, 2024)
This study investigates the effect of Peer-to-Peer (P2P) lending and market power on the stability of Islamic Commercial Banks (BUS). Stability is measured by the Z-score, and market power is measured by the Lerner Index. This study uses aggregate data from BUS, conventional bank, and P2P lending from January 2018 to December 2021. This quantitative research employs the Autoregressive Distributed Lag (ARDL) model. The results show that P2P lending does not affect BUS stability, whereas BUS market power has a positive effect on their stability. The implications of these findings suggest that while P2P lending is a rapidly growing competitor in the financial sector, its presence does not destabilize existing Islamic banks (BUS). Instead, BUS stability is more significantly influenced by their market power. Therefore, BUS should focus on enhancing their market power through strategic initiatives such as innovation in financial products, improving customer service, and increasing operational efficiencies.